Evaluation of the EndoPAT as a Tool to Assess Endothelial Function - M. Moerland; A. J. Kales; L. Schrier; M. G. J. van Dongen; D. Bradnock; J. Burggraaf (International Journal of Vascular Medicine)
Endothelial dysfunction is a potential target for (pharmaceutical) intervention of several systemic pathological conditions. We investigated the feasibility of the EndoPAT to evaluate acute changes in endothelial function with repeated noninvasive measurements and assessed its discriminating power in different populations. Endothelial function was stable over a longer period of time in renally impaired patients (coefficient of variation 13%). Endothelial function in renally impaired and type 2 diabetic patients was not decreased compared to healthy volunteers (2.9±1.4 and 1.8±0.3, resp., versus 1.8±0.5, P>0.05). The EndoPAT did not detect an effect of robust interventions on endothelial function in healthy volunteers (glucose load: change from baseline 0.08±0.50, 95% confidence interval −0.44 to 0.60; smoking: change from baseline 0.49±0.92, 95% confidence interval −0.47 to 1.46). This suggests that at present the EndoPAT might not be suitable to assess (changes in) endothelial function in early-phase clinical pharmacology studies. Endothelial function as measured by the EndoPAT could be physiologically different from endothelial function as measured by conventional techniques. This should be investigated carefully before the EndoPAT can be considered a useful tool in drug development or clinical practice.